2006
DOI: 10.1127/0003-9136/2006/0166-0199
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation of an aquatic invertebrate community subjected to avian predation at the Odiel salt pans (SW Spain)

Abstract: We studied the temporal variation in abundance and distribution of invertebrates in the water column in both traditional and industrial salt pans in the Odiel marshes, south-west Spain, in 2001. We selected 12 ponds that were representative of different salinities and stages of salt production. Every two months, invertebrates were sampled within the 0 -20 cm depth range used by foraging waders. We identified 40 taxa, including 30 aquatic and eight terrestrial metazoan invertebrates. Aquatic invertebrate taxa r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 42 publications
1
50
0
Order By: Relevance
“…and examined them for cestode infections. We selected this period because previous studies in the Odiel Saltpans showed that both Artemia abundance and levels of cestode infections reached maxima in the summer and early autumn (Sánchez et al 2006b;Sánchez et al, in preparation). The present study included three populations of the native parthenogenetic A. parthenogenetica and three populations of the invasive bisexual A. franciscana inhabiting salt pond complexes along the Atlantic coast of southern Portugal and Spain (Table 1; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…and examined them for cestode infections. We selected this period because previous studies in the Odiel Saltpans showed that both Artemia abundance and levels of cestode infections reached maxima in the summer and early autumn (Sánchez et al 2006b;Sánchez et al, in preparation). The present study included three populations of the native parthenogenetic A. parthenogenetica and three populations of the invasive bisexual A. franciscana inhabiting salt pond complexes along the Atlantic coast of southern Portugal and Spain (Table 1; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Artemia parthenogenetica is the dominant invertebrate in the evaporation ponds, where it is a major prey for waders, gulls, flamingos and grebes (Sánchez et al 2006). We used a 0.1-mm mesh net for collecting the sample.…”
Section: Methodsmentioning
confidence: 99%
“…For example, hypersaline salt ponds and lakes have unusually low invertebrate species richness and are often dominated by brine shrimp Artemia spp. as the main macroinvertebrate (Sánchez, Green & Castellanos, 2006). However, a diverse community of waterbirds preying on the shrimps maintains up to 15 species of cestodes within the Artemia population, each using a specific waterbird group as final hosts (Georgiev et al, 2005(Georgiev et al, , 2007.…”
Section: Supporting and Regulating Services (1) Biodiversity Of Omentioning
confidence: 99%